Comparison of Chemical Composition of Essential Oil Acquired from Single-Component Pharmaceutical Products, Food Products, and from the Cultivation of Sage Salvia officinalis L. from Poland. Issue 6 (2nd November 2021) - Kowalska, Grazyna; Baj, Tomasz; Kowalski, Radoslaw
Abstract: Sage is a common ingredient in herbal mixtures and is also found in the form of infusion bags. Due to its culinary qualities, it is also grown in gardens as a spice. In the present work, an analysis of the composition of essential oil from sage obtained from commercial products and our three-year cultivation was carried out. Hydro-distillation of essential oils was carried out according to the Polish Pharmacopoeia VIII. Qualitative and quantitative analysis of the essential oil was carried out by GC/MS and GC/FID. In the essential oils examined, the main components were: α-thujone (9.02-25.12 %), β-thujone (1.64-10.0 %), viridoflorol (6.60-16.63 %), α- humulene (2.94-10.77 %) and 1, 8-cineole (4.48-8.64 %). Sage is a popular spice, however, the use of this raw material may limit the content of α- and β-thujone, which may be toxic in high doses. Therefore, monitoring the content of these compounds in raw materials is very important. In our research, the best time to harvest sage was July in the second year of cultivation due to the lowest thujone content (15.78 % in total).